Corruption In Nigerian Society & The Insouciancing Of The Church In The Light Of Micah 3:9-12 - Bernard O. Itebiye (European Scientific Journal, ESJ, 2016)
This paper is a critical discourse on the seeming silence of the Church about the issue of Corruption in Nigerian Society, using Micah 3: 9-12 as a case study. It aimed at finding out the relevance of Prophet Micah’s massage to the contemporary Nigerian church and society in the light of the claim that Religion is necessary for morality, vis-à-vis the seeming damaging conclusion that many religious activities these days no longer impede corruption. The analyses employed Critical Discourse Analysis (CDA) framework. Data gathered both from the primary and secondary sources were analyzed through the hermeneutical, descriptive and analytical methods. The findings of the paper are that there is a high level of corruption in Nigerian Society and the Church is silent or saying little and that Corruption, in whatever name it is called, including its encouragement by insouciance, can affect the society in many ways. The paper is of the view that the church, like Micah in his time, cannot remain silent or seen to be promoting what it ought to condemn. The paper concludes that The Nigerian Political elites should be constantly reminded of such passages as Micah 6:8 where we are told that what the Lord truly requires of those who know him is “to love tenderly, to do justice, and to walk humbly before your God.” And that Religious leaders and organizations should be reminded that they can help turn many Nigerians away from what appears to be an incredibly high sense of devotion to the cult of material prosperity and material success towards the spiritual values of truth, justice, holiness and purity.